2004
DOI: 10.1086/383228
|View full text |Cite
|
Sign up to set email alerts
|

Bietti Crystalline Corneoretinal Dystrophy Is Caused by Mutations in the Novel Gene CYP4V2

Abstract: Bietti crystalline corneoretinal dystrophy (BCD) is an autosomal recessive retinal dystrophy characterized by multiple glistening intraretinal crystals scattered over the fundus, a characteristic degeneration of the retina, and sclerosis of the choroidal vessels, ultimately resulting in progressive night blindness and constriction of the visual field. The BCD region of chromosome 4q35.1 was refined to an interval flanked centromerically by D4S2924 by linkage and haplotype analysis; mutations were found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
275
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 232 publications
(294 citation statements)
references
References 21 publications
11
275
2
1
Order By: Relevance
“…Although the number of mutations identified in this study and Li et al, 5 40, is relatively small, some patterns do emerge when the ethnicity of the patients displaying those mutations is examined, especially the more common mutations. Of the 99 combined unrelated patients and families examined, the ethnicity of 13 of them was unknown, leaving 86: 31 of European origin, 38 of Chinese origin, 1 of Arabic origin, 8 of Korean origin, and 8 of Japanese origin (Table 3).…”
Section: Ethnic Origins Of Cyp4v2 Mutations In Bcd Patientscontrasting
confidence: 46%
See 4 more Smart Citations
“…Although the number of mutations identified in this study and Li et al, 5 40, is relatively small, some patterns do emerge when the ethnicity of the patients displaying those mutations is examined, especially the more common mutations. Of the 99 combined unrelated patients and families examined, the ethnicity of 13 of them was unknown, leaving 86: 31 of European origin, 38 of Chinese origin, 1 of Arabic origin, 8 of Korean origin, and 8 of Japanese origin (Table 3).…”
Section: Ethnic Origins Of Cyp4v2 Mutations In Bcd Patientscontrasting
confidence: 46%
“…included in this study were aligned along with those from Li et al, 5 Lin et al, 22 and Lee et al 23 as shown in Figure 2. The CAAT(delCT)TA (indel)TCA haplotype shaded in dark blue in homozygotes was the most common in Chinese, Japanese, and Koreans, and was assumed to be the ancestral haplotype for all three population groups.…”
Section: Cyp4v2 Mutations X Jiao Et Almentioning
confidence: 99%
See 3 more Smart Citations